The Implementation of Sustainable Event Management in Organizing International Music Concerts at the Jakarta International Stadium - Siti Adelita Raif Khadijah; Wiwik Dwi Pratiwi (Journal of Event, Travel and Tour Management, 2023)
Music concerts that are managed in a sustainable manner have significant value and can provide many benefits to the community and the destination where the concert takes place if the positive impact is cultivated. To achieve this great potential, continuous music concert event management must be widely adopted and expanded as a common practice. The establishment of the Jakarta International Stadium (JIS) as a multi-event and multi-function infrastructure has the potential to develop music tourism through concerts. This study uses a qualitative descriptive analysis method with secondary data sources in the form of literature studies and online publications. The aim of this study is to identify the potential of JIS as a music concert infrastructure, the roles and responsibilities of management for the sustainability of events at JIS, to describe sustainable concert management strategies that can be implemented at JIS. The output of this research generates insight and knowledge about the management of sustainable music concert events at JIS which can be used as a tourist attraction for domestic and foreign tourists. This study indicate that JIS is an event infrastructure that is ready to be used both in terms of facilities and management to develop music tourism through music concerts at JIS. Strategy of sustainable event management proposed in this study is specifically designed to be implemented based on the main roles and responsibilities of sustainable music concert management at JIS.